2018
DOI: 10.1002/adv.21943
|View full text |Cite
|
Sign up to set email alerts
|

Cassava starch‐graft‐poly(acrylonitrile)‐coated urea fertilizer with sustained release and water retention properties

Abstract: Cassava starch-graft-poly(acrylonitrile) samples were synthesized by a free radicalinitiated polymerization reaction, and urea fertilizer was coated with these grafted starches to obtain the dual benefit of sustained release and water retention properties.A response surface design was used to optimize the synthetic conditions of starchgraft-copolymers to maximize the slow nutrient release and water absorbency. The FT-IR analysis confirmed the grafting reaction, and scanning electron micrographs revealed the ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Sugar-based materials, such as starch, sucrose, and glucose, are some of the essential raw materials for the preparation of bioadhesives, which rely on their low cost, biodegradability, sustainability, nontoxicity, and easy availability . Recently, some research have been conducted on starch-based adhesives. Starch, made up of different proportions of amylopectin and amylose, is a polysaccharide being formed by thousands of linked glucose units.…”
Section: Introductionmentioning
confidence: 99%
“…Sugar-based materials, such as starch, sucrose, and glucose, are some of the essential raw materials for the preparation of bioadhesives, which rely on their low cost, biodegradability, sustainability, nontoxicity, and easy availability . Recently, some research have been conducted on starch-based adhesives. Starch, made up of different proportions of amylopectin and amylose, is a polysaccharide being formed by thousands of linked glucose units.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ibrahim et al [127] prepared the controlled-release nitrogen fertilizer using crosslinked corn starch with improved stability and mechanical strength. Jyothi et al [128] prepared cassava starch-graft-polyacrylonitrile-coated urea fertilizer, and the results exhibited the N release in the range of 69.8-78.3%. Apart from the fertilizers, modified starch was used in the preparation of agricultural mulch films.…”
Section: Applications Of Chemically Modified Starchmentioning
confidence: 99%
“…Agriculture Industry Crosslinking Controlled-release nitrogen fertilizer [127] Oxidization Starch-Based Antibacterial Nanocomposites [129] Grafting Polyacrylic acid graft-starch [130] Cassava starch-graft-polyacrylonitrile-coated urea fertilizer [128] Superabsorbents…”
Section: Applications Modification Techniques Examples Referencesmentioning
confidence: 99%
“…In the soil, this would be an important feature, since it would ensure slow penetration of water into the fertilizer, consequently releasing nutrients to the plants in a controlled manner. Harris (2009) reported that polymers produced with crosslinkers generally exhibit lower degrees of swelling, compared to those synthesized without crosslinking agents. Therefore, this test can also be used to indirectly assess crosslinking, since swelling depends on the degree of crosslinking of the material (Gehrke and Harsh 1991).…”
Section: Degree Of Swellingmentioning
confidence: 99%